Menuju Kesiapan Karier Optimal: Pendampingan Mahasiswa ke Dunia Kerja Melalui Pelatihan CV dan Simulasi Wawancara Kerja di Universitas Islam Internasional Darullughah Wadda’wah Putri Pasuruan - Ariyanti, Novi; Himsyah, Unun Zumairoh Asr (Universitas Islam Internasional Darullughah Wadda'wah, 2023)
Currently, there are so many bachelor’s/ graduates that it add to the barrage of task for instituyions and government to think about ways/ system so that existing job opportunities can absorb graduates, wich are always increasing every year. UII Dalwa provides one solution to prepare its graduates to be more easily accepted in the world of work through training in making applications, Curriculum Vtae (CV) and providing job interview skills. By using 3 stages in its imoementation, namely problem identification, implementation and evaluation, community service activities in the from of training were held and the results of this training were students ability to prepare applications, CV and the ability to answer job interviews.